Closantel; a veterinary drug with potential severe morbidity in humans. Issue 1 (December 2016) - Tabatabaei, Seyed; Soleimani, Mohammad; Mansouri, Mohammad; Mirshahi, Ahmad; Inanlou, Bahman; Abrishami, Mojtaba; Pakrah, Ahmad; Masarat, Hamideh
Abstract Background Closantel is a halogenated salicylanilide with a potent anti parasitic activity. It is widely used in management of parasitic infestation in animals, but is contraindicated in humans. Case presentation A 34-year-old man with depression was referred to our center with progressive loss of vision in both eyes 10 days after unintentional ingestion of three 500 mg tablets of Closantel. On fundus examination, left optic disc margin was blurred. His bilateral visual acuity was no light perception (NLP) despite prescribed IV erythropoietin injections 20, 000 units daily for 3 days and 1gr intravenous methylprednisolone acetate for 3 days followed by 1 mg/kg oral prednisolone. On macular optical coherence tomography (OCT), a disruption in outer retina was observed. Electroretinogram and visual evoked potential tests showed visual pathway involvement. Conclusions Destruction of neurosensory retina and visual pathways after accidental Closantel use is related to severe visual loss. This case alerts us about the destructive effect of this drug on humans even in low dosage which necessitates preventive efforts to reduce the chance of this morbid side effect.